Amaratunga v. Northwest Atlantic Fisheries Organization. (2017) - Unknown
Abstract : 618 International organizations — Immunities — Northwest Atlantic Fisheries Organization — Northwest Atlantic Fisheries Organization Privileges and Immunities Order, Section 3(1) — Absolute and limited immunities — Immunities and privileges as "required" for "performance of functions" — Meaning of "required" — Functions of international organizations — Whether lack of forum to air grievance defeating immunity — Labour relations — Whether immunity extending to internal Staff Rules Relationship of international law and municipal law — Human rights — Immunities — 1985 Canadian Bill of Rights, Section 2(e) — Right to a fair hearing — Privileges and Immunities (International Organizations) Act 1985 — Foreign Missions and International Organizations Act 1991 — Northwest Atlantic Fisheries Organization Privileges and Immunities Order Treaties — Immunities — International organizations — Convention on the Privileges and Immunities of the United Nations, 1946 — International Covenant on Civil and Political Rights, 1966, Article 14 — Right to a fair hearing — Procedural rights versus substantive rights — Whether right to make a claim — The law of Canada